Building the Future Internet Through FIRE : A Research and Experimentation Based Approach. - Serrano, Martin. (River Publishers, 2017)
The challenge for the Internet of the Future design is to build robust enabling technologies, implement and deploy adaptive systems, to create business opportunities considering increasing uncertainties and emergent systemic behaviors where humans and machines seamlessly cooperate.